Impact of Fixed Orthodontic Appliance and Clear Aligners on the Periodontal Health: A Prospective Clinical Study - Ada Carolina Pango Madariaga; Rosaria Bucci; Roberto Rongo; Vittorio Simeon; Vincenzo D'Antò; Rosa Valletta (MDPI AG, 2020)
This study aimed to evaluate the periodontal health of orthodontic patients with supportive periodontal therapy in a 3 month follow-up. The sample comprised 20 patients (mean age 20.6 ± 8.1 years) in treatment with multibracket fixed appliances (fixed group—FG) and 20 patients (mean age 34.7 ± 12.5 years) in treatment with clear aligners (clear aligners group—CAG). At baseline (T0) and after 3 months (T1), probing depth (PD), plaque index (PI), bleeding on probing (BOP), and gingival recession (REC) were measured. Patients were trained to perform an individualized tooth brushing technique, and every 2 weeks they were re-called to reinforce the oral hygiene instructions. The intra-group comparisons (T1 vs. T0) were calculated with the Wilcoxon signed-rank test, while a linear regression model was used for the inter-group comparisons (FG vs. CAG). The significance level was set at p < 0.05. Statistically significant decrease in both groups was found for PD (FG: Δ, −9.2 inter-quartile range (IQR), −22.5, −5.5; CAG: Δ, −12.6 IQR, −25.4, −4.8), BOP (FG: Δ, −53.5 IQR, −70.5, −37; CAG: Δ, −37.5 IQR, −54.5, −23), and PI (FG: Δ, −17.5 IQR, −62.5, 14.5; CAG: Δ, −24 IQR, −49.5, −5). The result of the linear regression models suggested that the type of appliance did not have any effects on the improvement of periodontal variables. Therefore, patients undergoing orthodontic treatment with fixed appliances and clear aligners did not show differences in gingival health when followed by a dental hygienist.